(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Power Quality has been said “a set of electrical boundaries that allow equipment to function in its intended manner without significant loss of performance”. Performance degradation results when the electrical power supplied to equipment is deficient. Thus power quality improvement is the main concern of present era. The problems of power quality are rising exponentially from the last few decades due to the rising demand for power and the need for their improvement is indeed a big question. The main power quality problems such as voltage sags and swells, power interruptions (short and long), voltage spike, harmonic distortion, noise have led to financial losses. To avoid huge losses and to overcome the above mentioned problems, power electronics has evolved with its new types of devices known as Custom Power Devices which are being reviewed in this paper.